Isolation and characterization of amber mutations in gene dnaA of escherichia coli K-12. - Schaus, N (1981)
Amber mutants with defects in the dnaA gene of Escherichia coli K-12 were isolated after localized mutagenesis of the tna-dnaA region of the chromosome. We isolated 36 mutants defective in the initiation of deoxyribonucleic acid replication as determined by their dependence upon integrative suppression by a P2 sig5 prophage. Three of the 36 mutants were shown to contain amber mutations through the use of a temperature-sensitive amber suppressor. These mutations, which mapped between gyrB and tna, were characterized genetically and biochemically as amber mutations in dnaA.